2018
DOI: 10.17796/1053-4628-42.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates of Stainless Steel Crowns and Multi-Surface Composite Restorations Placed by Dental Students in a Pediatric Clinic

Abstract: The study demonstrates that stainless steel crowns had a higher survival rate than multi-surface composite resins placed by students at a pediatric dental clinic in primary molars of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
1
10
0
3
Order By: Relevance
“…Stainless steel crowns are pre-formed metal crowns that have shown significant clinical success and are considered a favorable restoration method for multiple surfaces and larger carious lesions on primary molars [ 12 , 13 , 14 ]. Studies have evaluated the performance of stainless steel crowns in comparison to other restoration methods and found that stainless steel crowns showed a higher lifespan and durability [ 15 , 16 , 17 , 18 ]. The stainless steel crowns have reasonable costs and are less technique sensitive during placement [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steel crowns are pre-formed metal crowns that have shown significant clinical success and are considered a favorable restoration method for multiple surfaces and larger carious lesions on primary molars [ 12 , 13 , 14 ]. Studies have evaluated the performance of stainless steel crowns in comparison to other restoration methods and found that stainless steel crowns showed a higher lifespan and durability [ 15 , 16 , 17 , 18 ]. The stainless steel crowns have reasonable costs and are less technique sensitive during placement [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar study followed up a total of 6288 primary molar teeth restored with either composite resin or SSC restorations where the primary outcome was time to a new restoration or crown on the same tooth. 245 At 3 years, 1.5% of SSCs and 21% of 2-and 3-surface composite resin restorations required replacement resulting in a hazard ratio of 14.0 (95% CI=9-22, P<.001). In addition, 6.8% of the composite resin restorations required replacement with SSCs.…”
Section: Composite Resinsmentioning
confidence: 95%
“…Pulpektomi merupakan perawatan alternatif untuk memper-tahankan gigi sulung yang melibatkan pulpa di rongga mulut. [9][10][11] Pulpektomi merupakan teknik yang direkomendasikan untuk perawatan inflamasi pulpa ireversibel atau nekrosis yang disebabkan oleh trauma atau karies gigi, dan dianggap sebagai pilihan konservatif dibandingkan dengan pencabutan gigi. Tujuan utama perawatan endodontik adalah untuk memulihkan aspek fungsional dari gigi yang terkena dengan menyembuhkan atau menjaga integritas jaringan periapikal, dan juga menghilangkan mikroorganisme dari saluran akar untuk mencegah infeksi ulang berikutnya.…”
Section: Bahasanunclassified